STRATEGI MANAJEMEN LABA MELALUI PENERAPAN KEBIJAKAN AKUNTANSI DAN DERIVATIF - Nosami Rikadi (Jurnal Akuntansi Bisnis, 2017)
This Topic is to examine the effects of discretionary accounting accrual decision and financial derivative uses on earning management.  We investigate whether derivatives with hedging and discretionary accrual choices are used as income smoothing substitutes. We test this hypothesis with firms primarily engaged in oil exploration and drilling since we can identify two kinds of risks that can cause earnings volatility such as oil price risk and exploration risk.  The firms can hedge oil price risk with derivative instrument but there are no markets comparable to oil futures markets in which a firm can hedge the risks it bears for oil exploration.  Discretionary accrual choices can be used to reduce variability in earning induced by the exploration risk and both discretionary accruals and hedging can reduce earning variability associated with oil price fluctuation. However, we find that not all firms hedge all oil price risk they face, but instead appear to achieve some benchmark level of earning volatility.  The results show that firms are more likely to hedge the higher level of exploration they face.  And also suggest that firms use derivative and discretionary accruals as partial substitutes to smooth earnings.Keywords : Earning Management, Discretionary accrual, Hedging, Income smoothing